Influence of graft size matching on outcomes of infantile living donor liver transplantation. (23rd September 2015) - Wan, Ping; Li, Qigen; Zhang, Jianjun; Shen, Conghuan; Luo, Yi; Chen, Qimin; Chen, Xiaosong; Zhang, Ming; Han, Longzhi; Xia, Qiang
Abstract: We aimed to assess the impact of size mismatching between grafts and recipients on outcomes of infants or small children after LDLT. Between October 2006 and December 2014, 129 LDLT recipients weighing no more than 8 kg were retrospectively analyzed. The entire cohort was categorized into three groups by GRWR: GRWR<3.0% (group A, n = 38), 3.0%≤GRWR<4.0% (group B, n = 61), and GRWR≥4.0% (group C, n = 30). Baseline characteristics were similar among groups A, B, and C. Compared with groups A and B, post‐transplant alanine aminotransferase and aspartate aminotransferase within seven days were significantly higher in group C; however, differences between total bilirubin and albumin after transplantation were not prominent. Moreover, incidences of surgical complications, perioperative deaths, infections, and acute rejections were all comparable among the three groups. Five‐yr patient survival rates for groups A, B, and C were 89.5%, 88.9%, and 81.6%, respectively (p = 0.872), and the graft survival rates were 89.5%, 86.6%, and 81.6%, respectively (p = 0.846). In conclusion, GRWR between 1.9% and 5.8% would not cause noticeable adverse events for infantile LDLT recipients ≤8 kg. However, there is still a role for considering reduction in the graft mass as an applicable strategy in selected cases.